The Importance Of Fixed Assets and Leverage To Profitability In Transportation Companies - Anggi Putri Kusuma Wardini; Wiwin Sukiati; Indri Gustirani (Prodi Manajemen S1 dan D3 Keuangan & Perbankan, 2023)
Transport companies listed on the Indonesia Stock Exchange tended to experience a decline in profits, even not a few companies that suffered losses.The population in this study are transportation companies listed on the Indonesia Stock Exchange for the period of 2018 - 2020. By using the purposive sample method, there are 29 sample companies that were studied during the period 2018 - 2020. The results of this study indicate that partially asset turnover has a positive effect on profitability as measured by Return on Asset Ratio, these results are evidenced by the value of t count> t table (3.703> 1.99045) and the significance value <0.05 while there is a negative influence between leverage (Debt to Asset Ratio) to profitability (Return on Assets), evidenced by the results of statistical tests of the value of t count> t table (-4.316> 1.99045) and the significance value <0.05.